Advanced Electromagnetic Waves - Osman Bashir, Saad (IntechOpen, 2015)
This book endeavors to give the reader a strong base in the advanced theory of electromagnetic waves and its applications, while keeping pace with research in various other disciplines that apply electrostatics/electrodynamics theory. The treatment is highly mathematical, which tends to obscure the principles involved.